POLITIK ADMINISTRASI KEPENDUDUKAN DALAM PENYELENGGARAAN PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN PROBOLINGGO (Kalam: Jurnal Agama dan Sosial Humaniora, 2023)
Population administration is part of the state administration system, has an important role in government and the development of population administration. This study aims to describe the political aspects that can influence population administration in implementing public services in Probolinggo Regency. Using a descriptive descriptive research method. The results of the study show that the administration of population administration services at the Probolinggo Regency Population and Civil Registry Office already has a fairly comprehensive basis for statutory provisions. Service systems and procedures have been implemented in accordance with the standard provisions of Law Number 23 of 2006 concerning population administration, furthermore public service standards refer to Law Number 25 of 2009 concerning public services. Human resources in the delivery of public services are also quite good. This is proven through a survey of community satisfaction on the official website of the Probolinggo Regency Dispendukcapil, namely the community satisfaction index reaching 90.07. Which figure is classified as very good.